Investigating Human Centered Governance in Contemporary Public Organizations - Happy Susanto; Semuel Risal; Lulu Anastesi Sayekti; Sri Utami; Bernadeta Nefo Eka Wijayanti (Asian Journal of Applied Business and Management, 2026)
The increasing complexity of social, economic, and technological challenges has encouraged public organizations to adopt governance approaches that are more inclusive, participatory, and citizen-oriented. Human-centered governance has emerged as a contemporary paradigm that places citizens’ needs, experiences, and aspirations at the center of policymaking and public service delivery. This study aims to examine the concept, characteristics, principles, implementation, and contributions of human-centered governance in contemporary public organizations. The study employed a Narrative Literature Review (NLR) approach using secondary data obtained from peer-reviewed journals, academic books, policy documents, and reports from international organizations. Relevant literature was collected from major academic databases and analyzed through narrative thematic analysis. The findings indicate that human-centered governance is characterized by citizen orientation, participatory engagement, empathy-driven administration, adaptability, and cross-sector collaboration. Its implementation is reflected through human-centered service design, citizen participation platforms, organizational culture transformation, and data-informed yet human-sensitive decision-making. Evidence from Indonesia, particularly through SP4N-LAPOR! and SIASN, demonstrates growing efforts to strengthen citizen-centered governance.